2000
DOI: 10.3122/15572625-13-3-172
|View full text |Cite
|
Sign up to set email alerts
|

Are Yearly Physical Examinations in Adolescents Necessary?

Abstract: Background: Recommendations regarding the frequency of routine physical examinations for adolescents have varied from one examination every 2 to 3 years to yearly evaluations. Because none of these recommendations was based on studies regarding the usefulness of such examinations, it was pertinent to review the results of published studies.Methods: All series of routine school and preathletic examinations of adolescents published in the English literature from 1943 to 1995 were reviewed. Only reviews of examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In Finland, children are already thoroughly examined for this condition as well as other similar conditions such as heart murmurs [ 30 , 31 ] in health checks at the age of four years, in addition to earlier health checks in well-child clinics. These results are in line with a review in which annual physical examinations had no value in detecting important pathologic conditions in adolescents [ 10 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In Finland, children are already thoroughly examined for this condition as well as other similar conditions such as heart murmurs [ 30 , 31 ] in health checks at the age of four years, in addition to earlier health checks in well-child clinics. These results are in line with a review in which annual physical examinations had no value in detecting important pathologic conditions in adolescents [ 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…Substantial gaps exist in the evidence supporting many preventive care recommendations such as behavioral counceling and screening which are often included in health checks [ 9 ]. According to a review of research published in English from 1943 to 1995, yearly physical examinations had no value in detecting important pathologic conditions in adolescents [ 10 ]. The diagnostic accuracy of blood pressure measurements among asymptomatic children and the benefits and harm of screening for adolescent idiopathic scoliosis are unclear [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2000 meta-analysis by Stickler identified blood pressure, heart murmur, hernia, or undescended tests as the primary medical issues that came up in PPEs, but many without serious positive findings. 9 Our study showed a small number of student athletes failed their PPE due to medical or orthopedic issues. Most failures occurred due to a vision deficit, which could be addressed by encouraging parents to have their children undergo yearly vision screenings and partnering with the local community for resources to assist in not only screenings but access to corrective lenses.…”
Section: Discussionmentioning
confidence: 68%
“…4 The percentage of DQ and CR athletes aligns with that in the current literature; historically, providers disqualify 1% of student-athletes and refer 1%–13% further evaluation during PPEs. 22 , 23 Similarly, in 2018, NCH sports medicine disqualified 3% of our student-athletes and recommended further follow up for 11%. In the end, only 1 student-athlete remained disqualified at 4 months.…”
Section: Discussionmentioning
confidence: 99%